2021
DOI: 10.1021/acsami.1c18155
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Gallium Sulfide as a Novel Saturable Absorber for Broadband Ultrafast Photonics Applications

Abstract: Two-dimensional (2D) gallium sulfide (GaS) offers a plethora of exceptional electrical and optical properties, allowing it to be used in a wide range of applications, including photodetectors, hydrogen generation, and nonlinear optical devices. In this paper, ultrathin 2D GaS nanosheets are synthesized using the liquid-phase exfoliation method, and the structure, morphology, and chemical composition of the as-prepared nanosheets are extensively investigated. After depositing 2D GaS nanosheets on side polished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Figure a,b shows the GaS crystal structure from the side and top views. Generally, GaS crystallizes in the hexagonal P 6 3 / mmc space group . The GaS crystal lattice is constructed of covalent bonds between Ga–Ga and Ga–S, which stretch in two dimensions, resulting in a stratified crystal composed of planes bound together by van der Waals attractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a,b shows the GaS crystal structure from the side and top views. Generally, GaS crystallizes in the hexagonal P 6 3 / mmc space group . The GaS crystal lattice is constructed of covalent bonds between Ga–Ga and Ga–S, which stretch in two dimensions, resulting in a stratified crystal composed of planes bound together by van der Waals attractions.…”
Section: Resultsmentioning
confidence: 99%
“…The bulk of GaS has the indirect bandgap (2.5 eV) opposite to some transition-metal dichalcogenides (TMDs) like MoS 2 , and the monolayer has an indirect bandgap of 3.43 eV. This wide bandgap of GaS facilitates its possibility to be utilized in significant applications like photodetectors, flexible electronics, hydrogen evolution catalysis, terahertz generation, solar energy conversion, and nonlinear optics. Recently, GaS thin films have demonstrated a considerable variation in NLO behavior as a result of their phase transition features . Additionally, our previous experimental investigation showed that GaS nanosheets could be utilized as saturable absorbers to obtain broadband mode-locking operations in Yb-, Er-, and Tm-doped fiber laser systems covering wavelengths from 1 to 2 μm . These studies indicate the applicability of 2D GaS for broadband ultrafast photonics devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these nanomaterials have been used in many other photothermal 36 40 and optical device applications. 41 43 Among these, MWCNTs possess the potential to be used to design wide bandwidth patch antenna due to their superior alternating current conductivity and electromagnetic wave interactions. Since the discovery of the MWCNTs in 1991, they has demonstrated their superiority in the wide range of applications because of their superior electromechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have investigated the use of microstrip patch antennas for the early detection of breast cancer, , brain tumor, , lung cancer, and many other biomedical applications. , Patch antennas are preferred over others for biomedical applications due to their low weight, thin profile, linear and circular polarization, dual and multi-frequency operation capacity, and ease of fabrication. Different materials are frequently used in patch antenna design, such as copper, gold, and aluminum. , However, the use of these conventional materials usually provides narrow bandwidth. , In recent years, many research groups have explored nanomaterials such as graphene, ZnO nanorods, TiO 2 , multiwall carbon nanotubes (MWCNTs), , and so forth, designing the radiating element of the patch antenna. Besides, these nanomaterials have been used in many other photothermal and optical device applications. Among these, MWCNTs possess the potential to be used to design wide bandwidth patch antenna due to their superior alternating current conductivity and electromagnetic wave interactions. Since the discovery of the MWCNTs in 1991, they has demonstrated their superiority in the wide range of applications because of their superior electromechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Different atomic structures of GaS can be obtained by different growth methods [54][55][56]. Considering the application potential of GaS in the field of nonlinear optics, there is a strong motivation for one to improve the quality of GaS in terms of size and purity [57].…”
Section: Introductionmentioning
confidence: 99%